Effects of Spirulina Meal Supplementation On Growth and Survival Rate of Royal Whiptail Catfish Fry (Sturisoma panamense) - Firdausi, Amalia Putri; Mauladina, Annas Yudha; Rahman, Rahman; Prama, Ega Adtiya; Tunisah, Risma Arafah (Department of Aquaculture, 2025)
Royal Whiptail Catfish (Sturisoma panamense) have high-stress levels in the early stages of their life. This is a significant concern in the field of fish farming. One of the crucial factors in the cultivation of royal whiptail catfish is the addition of vegetable or algae protein to the feed according to the habits of herbivorous fish. This study aimed to determine the best dose of spirulina that can enhance the growth and survival rates of royal whiptail catfish fry. There were four treatment groups, i.e. feed without spirulina (K), a dose of 3% (SP-3%), a dose of 6% (SP-6%), and a dose of 9% (SP9%). The study was conducted at the Tetra Aquaria Company in Sukabumi City in April - May 2024. The spirulina culture was dried in an oven at 60 ℃ for 24 hours and ground using a mortar. The powdered feed was mixed with spirulina according to the treatment dose. The fish larvae used were newly hatched larvae, and the maintenance period during the treatment was 21 days. The maintenance container uses a tray measuring 40 cm x 30 cm x 15 cm. The study results showed that the best group was SP-6% with an average survival rate of 87% ± 4.62, significantly different compared to the K, SP-3%, and SP-9% treatments. The daily growth rate value of SP-9% showed the best significant difference (P <0.05) from the control treatment and 3% dose, however not significantly different (P> 0.05) with SP-6%.